The effect of corrective exercises on developing the accuracy of forehand and backhand strokes in squash players - Al-Tai, Prof. Dr. Ali Attia Dakhil; Dakheel, Asst.L. Hassanein Obeid (Sulaimani Journal for Humanities, 2025)
The research problem was identified based on the researchers' scientific experience in squash training. These skills, considered among the most prominent in squash, were chosen due to their importance in the superiority of individual players or competing teams. They are also among the most effective means of direct pressure, and players who master the forehand and backhand strokes, especially junior players, are able to win matches. Powerful and effective strokes earn the player a direct point. Furthermore, playing racket sports, including squash, is crucial due to the ability to score points. Therefore, the research highlights the importance of corrective exercises and their impact on learning the forehand and backhand stroke skills for squash players under 16-17 years old. These exercises play a significant role in raising the level of performance in this skill, particularly among young players. The research objectives focused on developing corrective exercises to improve the accuracy of the forehand and backhand strokes for squash players under 16-17 years old. These exercises were prepared and implemented by the researchers in educational units. The effect of these exercises on developing the skill performance of the forehand and backhand strokes in squash players was investigated. This research was conducted on a sample of players from the national team's training center at the College of Physical Education and Sports Sciences, University of Baghdad, totaling (16) players. They were divided into two equal groups, one experimental and the other control, each consisting of (8) players, after homogenization and equivalence processes. Appropriate tests for this skill were selected, and a small pilot study was conducted on a group of young squash players outside the main research sample, using the necessary research tools and methods. Pre-tests were administered to both groups, and then the skill exercises were implemented within (12) training units, each lasting (90) minutes. The exercises within the main part of the training unit amounted to (30) minutes. After the completion of the training units for this skill, post-tests were conducted, and the research results were analyzed using appropriate statistical methods. The researcher drew several conclusions. The most important finding was that the exercise vocabulary used had a positive impact on developing the accuracy of the forehand and backhand strokes of squash players. Moreover, the motor and physical qualities associated with the speed of motor response, despite their difficulty, can be developed and utilized in developing the technical performance and accuracy of skills in squash. In light of these conclusions, the researchers recommended the necessity of emphasizing the development of the accuracy of the forehand and backhand strokes in the early stages of sports training, because training on them in later stages requires a long time and great effort from players and coaches. Also, conducting research and studies on other motor qualities due to their great importance in developing the technical performance and accuracy of squash players in particular and other sports in general.
Keywords: Corrective exercises; forehand and backhand strokes; squash